Comfort women and sex in the battle zone - Hata, Ikuhiko, 1932- (Hamilton Books, 2018)
Comfort Women and Sex in the Battle Zone is an exhaustive examination of the controversial issue of comfort women, who provided sexual services to Japanese soldiers before and during World War II. This book provides extensive documents and narratives by witnesses to shed light on the reality of these women who worked in the battle zone.
Keywords: Comfort women -- Asia -- History.; Service, Compulsory non-military -- Asia.; World War, 1939-1945 -- Women -- Asia.; Women and war -- Asia -- 20th century.; Femmes de réconfort -- Asie -- Histoire.; Réquisitions civiles -- Asie.; Guerre mondiale, 1939-1945 -- Femmes -- Asie.; Femmes et guerre -- Asie -- 20e siècle.; HISTORY -- Europe -- Western.; Women and war; Comfort women; Women; Asia; Service, Compulsory non-military; 1900-1999; History